The Effect of Service Quality on Customer Satisfaction at Koperasi Karyawan PT. Lotus Indah Textile Industry - Damarsari Ratnasahara Elisabeth; Akhmad Nasir; Joko Suyono (LPPM of NAROTAMA UNIVERSITY)
This type of research uses a correlation coefficient, the sample used in this study is members who are also customers of Koperasi Karyawan PT. Lotus Indah Textile Industry in Surabaya as many as 50 customers who actively transact as many as 5 to 6 times each month. Processing data using validity test, reliability test and hypothesis test using t-test. The results of the correlation coefficient analysis using the SPSS 22.0 program amounted to 0.544 which means that there is an influence between employee service quality (x) on customer satisfaction (y). The results of the discussion and the results of testing the independent variable (x) service quality with dependent variables (y) customer satisfaction that H0 is rejected and H1 is accepted, because with t-count of 4.4917 > t table of 1.6672. This means that there is an influence of variable (x) on variable (y).